Can coenzyme Q10 supplementation effectively reduce human tumor necrosis factor-α and interleukin-6 levels in chronic inflammatory diseases? A systematic review and meta-analysis of randomized controlled trials. (October 2019) - Farsi, Farnaz; Heshmati, Javad; Keshtkar, Abbasali; Irandoost, Pardis; Alamdari, Naimeh Mesri; Akbari, Abolfazl; Janani, Leila; Morshedzadeh, Nava; Vafa, Mohammadreza
Graphical abstract: Abstract: Background/objective: Systematic inflammation plays a major role in all stages of chronic diseases. Recent evidence suggests that Coenzyme Q10 (CoQ10), as an anti-inflammatory agent, has shown beneficial effects on the inflammatory process of various human diseases. However, several trials have examined the effects of CoQ10 on pro-inflammatory cytokines with contrasting results. The objective of this systematic review and meta-analysis of randomized clinical trials (RCTs) was to assess the efficacy of CoQ10 supplementation on tumor necrosis factor- α (TNF-α) and interleukin-6 (IL-6) levels. Materials and methods: A systematic literature was performed on databases including PubMed/Medline, EMBASE, Web of Science, SCOPUS, Cochrane Library databases, Clinical Trials.gov and historical search of reference lists from selected studies up to December 2018. Two reviewers independently investigated study eligibility, extracted data, and assessed risk of bias of relevant studies using a standardized protocol. Heterogeneity was measured by the I 2 statistic. Data were pooled, using the ﬁx or random-effect model based on the heterogeneity test results and the efficacy of CoQ10 expressed as the standardized mean difference (SMD) with 95% conﬁdence interval (CI). Random-effects meta-regression was done to examine the effect of putative confounders or potential moderators on TNF-α and IL-6 levels. Results: Overall, nine RCTs with a total of 509 patients (269 in the CoQ10 arm and 240 in the control arm) provided the inclusion criteria and were included in the analysis. Our meta-analysis indicated that oral CoQ10 supplementation (60–500 mg/day for 8–12 weeks) resulted in significant reduction of TNF-α (SMD: −0.44, 95% CI: [−0.81 to −0.07] mg/dl; I 2  = 66.1%, p  = 0.00) and IL-6 levels (SMD: −0.37, 95% CI: [−0.65 to −0.09]; I 2  = 57.2, p  = 0.01), respectively. Subgroup analyses represented a significant reduction of TNF-α and IL-6 levels in patients with BMI < 26. Due to the small number of studies and patients included in each subgroup, these subgroup analyses need to be interpreted cautiously. Conclusion: This meta-analysis of RCTs reported a significant effect of CoQ10 on some of the inflammatory markers among patients with chronic diseases which could attenuate the inflammatory state. However, well-designed studies with a larger sample size are required. Note that the results should be interpreted with caution because of the evidence of heterogeneity and limited number of studies.